T Cell Deficits and Overexpression of Hepatocyte Growth Factor in Anti-inflammatory Circulating Monocytes of Middle-Aged Patients with Bipolar Disorder Characterized by a High Prevalence of the Metabolic Syndrome - Vogels, Rogier J.; Koenders, Manja A.; van Rossum, Elisabeth F. C.; Spijker, Annet T.; Drexhage, Hemmo A. (Frontiers in Psychiatry, 2017)
Background: We previously reported T cell deficits and pro-inflammatory gene activation in circulating monocytes of two cohorts of Bipolar Disorder (BD) patients, a cohort of postpartum psychosis patients and in bipolar offspring. Pro-inflammatory gene activation occurred in two clusters of mutually correlating genes, cluster 1 for inflammation related cytokines/factors, cluster 2 for motility, chemotaxis and metabolic factors. Aim: To verify these cellular immune abnormalities in yet another cohort (the BiSS cohort) of relative old (52 years, median) BD patients and to relate immune abnormalities to hair cortisol levels, measured in this cohort and representing long-term systemic cortisol levels, and to the presence of the metabolic syndrome (MetS), which was prevalent in 29% of the BiSS patients. Methods: Monocyte immune gene activation (Q-PCR) and T cell deficits (FACS analysis) were determined in 97 well-controlled, largely euthymic BiSS BD patients. Monocyte genes included the cluster 1 and 2 genes, the genes for the glucocorticoid receptor (GR)α and GRβ and the gene for hepatocyte growth factor (HGF, a marker of monocyte-derived Circulating Angiogenic Cells, CACs). CACs serve vessel repair. Abnormal numbers are found in patients with MetS and vascular damage. Results: As compared to healthy controls 1) The pro-inflammatory cluster 1 genes were down regulated and the GRα and the HGF gene upregulated in the monocytes of the BiSS patients, 2) T cell deficits were shown (reduced numbers of lymphocytes in particular of T cells). Within the reduced T cell population a shift had taken place in the T helper populations: Th17 increased, T regulatory cells decreased. Correlations between hair cortisol, the MetS, monocyte gene activation and T cell deficits were not found. Conclusion: T cell deficits most likely are a trait phenomenon of BD, since they have also been found in the other cohorts of BD patients and in bipolar offspring. Monocytes of this cohort showed an anti-inflammatory set point, suggesting that pro- and anti-inflammation are state characteristics of BD. The monocyte gene profile indicated an increased CAC activity; the question arises whether this is due to putative vessel damage in these relatively old patients with a high prevalence of the MetS.